2004
DOI: 10.1111/j.0022-202x.2004.23221.x
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Depletion Upregulates Involucrin Expression in Epidermal Keratinocytes Through Activation of p38

Abstract: Cholesterol has been recently suggested to regulate the early steps of keratinocyte differentiation through lipid rafts. In many cell types, depletion of cholesterol activates signaling proteins like epidermal growth factor receptor (EGFR), human epidermal growth factor receptor 2 (HER2), or extracellular signal-regulated kinase (ERK) known to affect cell differentiation. In this study, we explored the effects of cholesterol depletion on the phenotype of cultured keratinocytes, using a treatment with methyl-be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
80
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(89 citation statements)
references
References 75 publications
9
80
0
Order By: Relevance
“…5A, row 4), The co-localization of caveolin-1 and CT-B was much less conspicuous than in HK and this image was very similar to the image of SLO-HK. The presence of lipid rafts was reflected in the cell morphology; CD treatment caused shrinkage and rounding of the cells, as previously reported [31]. This shape change, which was reversed when Chol was replaced, may be related to the known disruption of the actin cytoskeleton by CD [32].…”
Section: Lipid Raft Content Of Membranes Is Altered In Slo-hksupporting
confidence: 72%
“…5A, row 4), The co-localization of caveolin-1 and CT-B was much less conspicuous than in HK and this image was very similar to the image of SLO-HK. The presence of lipid rafts was reflected in the cell morphology; CD treatment caused shrinkage and rounding of the cells, as previously reported [31]. This shape change, which was reversed when Chol was replaced, may be related to the known disruption of the actin cytoskeleton by CD [32].…”
Section: Lipid Raft Content Of Membranes Is Altered In Slo-hksupporting
confidence: 72%
“…Epidermal growth factor receptor (11), human ErbB2 (11), ERK (11-13), p38 (11,14), Src (15), and ␤-catenin (16) are activated by M␤CD treatment in various cell types. Like other cell lines, MCF-7 cells showed increased ERK phosphorylation following M␤CD treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Effect of M␤CD on Akt and p70S6K Phosphorylation-Cholesterol depletion by M␤CD has been suggested to cause changes in the phosphorylation of signaling molecules like ERK and Src (11,15). Using a phosphokinase array we screened the phosphorylation profiles of 46 kinases and their substrates to find out if M␤CD affected the signaling pathways important in HAS2 regulation.…”
Section: M␤cd Does Not Change the Size Of Hyaluronan Produced By Mcf-7mentioning
confidence: 99%
See 1 more Smart Citation
“…45 Altogether, these data suggest a role for p38δ isoform in activation of differentiation-dependent involucrin gene expression. However, the induction of involucrin expression by treatment with cholesterol-depleting agents involves p38α, 46 and constitutively active MEK6 or MEK7, when overexpressed in keratinocytes, increase involucrin via a mechanism that involves p38α, 42,47 suggesting that the engagement of a specific p38 isoform may be stimulus-dependent. Interestingly, a genomic analysis has shown that MAPK13 (a gene that encodes p38δ protein) and involucrin are among genes commonly upregulated both in psoriasis, a benign inflammatory condition characterized by increased proliferation and differentiation, and in well-differentiated locally invasive cutaneous squamous cell carcinomas (SCC).…”
Section: Introductionmentioning
confidence: 99%